Fully Covered Stent-TIPS for Advanced HCC Patients with Portal Vein Tumor Thrombus-Related Severe Symptomatic Portal Hypertension - Liu Z; Lyu T; Yang J; Xie Y; Fan S; Song L; Zou Y; Wang J (Journal of Hepatocellular Carcinoma)
Zechuan Liu,1,* Tianshi Lyu,1,* Jinming Yang,2 Yong Xie,1 Siyuan Fan,1 Li Song,1 Yinghua Zou,1 Jian Wang1 1Department of Interventional and Vascular Surgery, Peking University First Hospital, Beijing, People’s Republic of China; 2Department of Vascular Interventional, Aerospace Central Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Wang; Yinghua Zou, Department of Interventional and Vascular Surgery, Peking University First Hospital, Beijing, People’s Republic of China, Email wangjianbdyy@126.com; Dr_zouyinghua@126.comPurpose: Portal vein tumor thrombus (PVTT)–related severe symptomatic portal hypertension (SPH) leads to a poor prognosis in patients with advanced hepatocellular carcinoma (HCC). Traditional transjugular intrahepatic portosystemic shunt (TIPS) using covered plus bare stent can effectively relieve SPH, however, the bare segment is susceptible to obstruction due to PVTT invasion. This study aimed to evaluate the safety and efficacy of fully covered stent-TIPS (FCS-TIPS) for treatment of PVTT-related SPH in advanced HCC patients.Patients and Methods: This retrospective study enrolled 25 patients with advanced HCC who underwent FCS-TIPS for PVTT-related severe SPH from June 2018 to January 2024. The evaluated outcomes included overall survival (OS), technical success rate, reduction in portal venous pressure gradient (PPG), stent patency rate, SPH control rate, liver function and complications.Results: The technical success rate was 100% without perioperative deaths or severe procedure-related adverse events. The average PPG decreased by 13.4± 4.6 mmHg. The overall symptom control rate of SPH was 96.0%. Variceal bleeding, ascites/hydrothorax, and enteropathy control rates were 100%, 95.0%, and 100%, respectively. Liver function showed mild improvement one month after TIPS. One patient (4.0%) experienced overt hepatic encephalopathy (OHE) and three (12.0%) patients developed shunt dysfunction during the follow-up period. None of the patients experienced shunt-induced extrahepatic metastasis. The median OS was 6.0 months and the cumulative survival rates at 3, 6, 12 months were 80.0%, 52.0% and 21.3%.Conclusion: FCS-TIPS is safe and effective for treating PVTT-related severe SPH and can serve as a bridging therapy for advanced HCC.Keywords: fully covered stent, transjugular intrahepatic portosystemic shunt, hepatocellular carcinoma, portal vein tumor thrombus, symptomatic portal hypertension